Ethnomedicinal Review of Phyllanthus urinaria (Bhumyamlaki) - Deshpande, Mangirish N. (Current Overview on Pharmaceutical Science Vol. 3, 2023)
Phyllanthus urinaria commonly known as Bhumyamlaki has tremendous importance in folk medicine. It has been used traditionally as treatment of cough, haemorrhoids, dysentery and as liver tonic. The plant has paved the way for several new pharmacological experimental investigations. Several phytoconstituents belonging to group lignans, tannins, flavonoid, triterpenes have been isolated from the plant. This review is carried out to compile the research work carried out on the plant and to explore posse new research avenues.